Sickle Cell Anemia; 3 years clinical experience in Bisha, Saudi Arabia (2010-2013) - Aziz, Yahya; Musharraf, Warda; Hussain Shah, Syed Ibrar; Muhammad Teyab (International Journal of Endorsing Health Science Research, 2017)
Objective: Three-year clinical experience of patients diagnosed with Sickle cell disease in Bisha, South Western region of Saudi Arabia is analyzed. Methodology: A retrospective analysis was done on data recruited from 2011 to 2013 of all the patients presented with sickle cell anemia. The demographic data, clinical presentation, course of disease, complications and chronic conditions were collected. The descriptive percentage of data with years of presentation and its incidence rate per 100 person-years were also taken with the cause mortality. Results: Total 386 patients were analyzed, among them 45.2% were females and 54.8% were males. According to our study, the sickle cell crises included as acute chest syndrome (26%), pulmonary hypertension (21%), Splenomegaly (7%), septicemia (11%), acute Vaso-occlusive crisis (10%), and other sickle cell crisis (2-10%) of patients. It was also found that about 48% of patients suffered from 1 or more irreversible organ damage. The survival rate of male and female are not significant, however total 82 patients died of sickle cell anemia. Conclusions: Sickle cell disease represents high mortality in Saudi Arabia, comprising distinctive diseases characteristic in different regions. The qualitative and quantitative study of genetic and environmental factors in relation to disease complications need to be done.